Rehabilitation of notched circular hollow sectional steel beam using CFRP patch - Setvati, M.R. (Techno Press, 2018)
The application of carbon fiber reinforced polymer (CFRP) composites for rehabilitation of steel structures has become vital in recent years. This paper presents an experimental program and a finite element (FE) modelling approach to study the effectiveness of CFRP patch for repair of notch damaged circular hollow sectional (CHS) steel beams. The proposed modeling approach is unique because it takes into account the orthotropic behavior and stacking sequence of composite materials. Parametric study was conducted to investigate the effect of initial damage (i.e., notch depth) on flexural performance of the notched beams and effectiveness of the repair system using the validated FE models. Results demonstrated the ability of CFRP patch to repair notched CHS steel beams, restoring them to their original flexural stiffness and strength. The effect of composite patch repair technique on post-elastic stiffness was more pronounced compared to the elastic stiffness. Composite patch repair becomes more effective when the level of initial damage of beam increases. Copyright Â© 2018 Techno-Press, Ltd.